2006
DOI: 10.1200/jco.2005.05.1003
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab-CHOP Versus CHOP Alone or With Maintenance Rituximab in Older Patients With Diffuse Large B-Cell Lymphoma

Abstract: Rituximab administered as induction or maintenance with CHOP chemotherapy significantly prolonged FFS in older DLBCL patients. After R-CHOP, no benefit was provided by MR. These results, which are consistent with an additive effect of rituximab, suggest that future studies could focus on maintenance strategies with novel agents as well as new induction therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

38
815
8
10

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,226 publications
(871 citation statements)
references
References 30 publications
38
815
8
10
Order By: Relevance
“…The rate of cardiac toxicity recorded in our study is also among the lowest recorded when compared with results of other trials investigating R-CHOP, or R-CHOP-like regimens, in elderly patients with DLBCL. 18,[30][31][32]44 In our study, multivariate analysis revealed that the need for chemotherapy dose reduction was the only predictive factor of poor outcome, independently of age. Back in the days of first-generation chemotherapeutic regimens, when in a Southwest Oncology group (SWOG) study CHOP chemotherapy was reduced by 50% in patients over 65 years of age, CR rates declined.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The rate of cardiac toxicity recorded in our study is also among the lowest recorded when compared with results of other trials investigating R-CHOP, or R-CHOP-like regimens, in elderly patients with DLBCL. 18,[30][31][32]44 In our study, multivariate analysis revealed that the need for chemotherapy dose reduction was the only predictive factor of poor outcome, independently of age. Back in the days of first-generation chemotherapeutic regimens, when in a Southwest Oncology group (SWOG) study CHOP chemotherapy was reduced by 50% in patients over 65 years of age, CR rates declined.…”
Section: Discussionmentioning
confidence: 89%
“…18,30 However, the median age of patients enrolled in the R-CHOP phase III registration trial (GELA study) was only 69 years, and patients aged >80 years were not included in the trial. 18 Other reports showed that nonHodgkin lymphoma patients !70 years are more prone to encounter serious adverse events with R-CHOP than younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Effector mechanisms include complement-mediated cytotoxicity, antibody-dependent cellular cytotoxicity, and possibly direct induction of apoptosis [1,2]. In diffuse large B cell lymphomas (DLBCLs) and follicular lymphomas (FLs), several multicenter prospective randomized trials consistently demonstrated an improved outcome when R was added to chemotherapy [3][4][5][6][7][8][9][10]. In FL and DLBCL, it was attempted to further prolong response duration and survival by administering R during remission as maintenance therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In FL and DLBCL, it was attempted to further prolong response duration and survival by administering R during remission as maintenance therapy. In DLBCL, Habermann et al [6] performed a study in patients 60 years of age and older who were initially randomized for chemotherapy with cyclophosphamide, hydroxydaunorubicin, vincristine, and prednisone (CHOP) versus CHOP plus R (R-CHOP). Responding patients underwent a second randomization for R maintenance versus observation only.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation